The Application of Social Cognitive Theory on Tertiary Preventive Behavior in Elderly with Type 2 Diabetes Mellitus: A Multilevel Analysis - Amanda Widyarahma; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Diabetes Mellitus is a chronic disease whose prevalence increases, especially in old age. About a quarter of people over the age of 65 suffer from diabetes. DM can cause serious complications up to death. The importance of tertiary preventive behavior to prevent complications. This study aimed to analyze the influence of the Social Cognitive Theory construct and the contextual influence of posyandu on the tertiary preventive behavior of elderly people with type 2 diabetes mellitus. Subjects and Method: A cross-sectional study was conducted at 25 integrated health posts (posyandu) in Magetan, East Java, Indonesia, from April to May 2024. 200 elderly with type 2 DM were selected by stratified random sampling. The dependent variable was tertiary preventive behavior. The independent variables were self-regulation, knowledge, expectations, self-efficacy, reinforcement, and observational learning. Data collection was carried out by interviews and questionnaires. The data were analyzed using a multiple multilevel linear regression. Results: Tertiary preventive behavior was higher in self-regulation (b= 0.24; 95% CI= 0.01 to 0.46; p= 0.038), knowledge (b= 0.70; 95% CI= 0.23 to 1.17; p= 0.003), expectations (b= 0.53; 95% CI= 0.35 to 0.71; p <0.001), self-efficacy (b= 0.39; 95% CI= 0.11 to 0.67; p= 0.006), reinforcement (b= 1.26; 95% CI= 0.90 to 1.62; p<0.001), and observational learning (b= 0.30; 95% CI= 0.01 to 0.59; p= 0.036). There were no significant relationships of age and gender on tertiary preventive behavior. There was a contextual effect of elderly posyandu on tertiary preventive behavior (ICC= 6.39%). Conclusion: Tertiary preventive behavior is higher in self-regulation, knowledge, expectations, self-efficacy, reinforcement, and observational learning. There are no significant relationships of age and gender on tertiary preventive behavior. There is a contextual effect of elderly posyandu on tertiary preventive behavior.